Mobile Robot Navigation Using Planning Algorithm and Sliding Mode Control in a Cluttered Environment - Islem Reguii; Imen Hassani; Chokri Rekik (Universitas Muhammadiyah Yogyakarta, 2022)
The research contribution of the present work is to solve the path planning and path tracking problems in static and dynamic environments. A new Planning Navigation Algorithm Technique is developed in order to solve the problem of navigation with obstacle avoidance. The basic idea of this algorithm searches for a safe path for navigation. First, this algorithm is focused to identify an optimal collision-free route to a spatially defined objective. Then, in each displacement, the developed algorithm handles to maximize the distance between the obstacles and minimize the distance to the goal. This is to obtain the optimal trajectory for navigation. On the other side, a sliding mode controller is adopted to solve the tracking trajectory task. The basic idea of this control system is to allow the robot mobile to track the desired trajectory with minimum error. In addition, the comparative study between the proposed approach and the previous work is presented in order to demonstrate the satisfaction of the proposed strategy. Finally, simulation results which are developed using Matlab software are presented to show the robustness and efficiency of the developed algorithm and the reactivity of the proposed sliding mode controller.